Oral pyogenic granuloma at different spots: A series of case reports - Tanvi Phull; Hima Dadhwal; Rajpreet Kaur; Ritu Malhotra; Divya Jyoti; Ravneet Kaur (Wolters Kluwer Medknow Publications, 2024)
Pyogenic granuloma is an inflammatory non-neoplastic lesion of the oral cavity. Chronic, mild, local irritation, trauma, hormonal variables, and certain medications are typical causes of pyogenic granulomas. Women have a higher prevalence than men. The risk is greatest in the second to fifth decades of life. Clinically, the lesion appears smooth, with soft to firm consistency and nontender with a pedunculated or sessile base. Various modalities have been proposed for the treatment of lesion, which include the conventional approach, the use of laser, cryotherapy, and electrocauterization. This case series discusses three cases of pyogenic granuloma in female patients at different locations in the oral cavity. The lesion was subsequently treated with electrosurgery and surgical convention methods. No recurrence of the lesion has been seen in either of the cases.